The impact of lean six sigma program on the performance standards of pre-hospital emergency: A semi-experimental study - Ehsan Koshki; Mohammad Zarezadeh; Khadijeh Nasiriani (Preventive Care in Nursing and Midwifery Journal)
Background: Emergency medical services (EMSs) organize care provided to patients in out-of-hospital settings, playing a crucial role in minimizing physical and psychological harm resulting from diseases and emergencies. Consequently, pre-hospital emergency is an integral component of healthcare systems, requiring performance standards to improve outcomes for injuries and other illnesses. Thus, the effective utilization of modern management methodologies is essential in this context. Objectives: The current study aimed to determine the impact of the Lean Six Sigma (LSS) program on performance standards of pre-hospital emergency. Methods: This single-group quasi-experimental study with a pretest-posttest design was conducted on 50 pre-hospital emergency personnel in Koohdasht County in 2023 using a census method. The research tool included a performance standard measurement checklist, completed through observation before and after implementing the LSS method. Data were analyzed using the paired t-test in SPSS v.18 software. Results: The findings revealed that the majority of participants held bachelor’s degrees (54%), were contractual employees (56%), and were all male. There was a statistically significant difference in the mean score of the performance standards in the personnel (p=0.001), equipment (p<0.001), and overall (p<0.001) dimensions before and after the intervention. Conclusion: Based on the findings, the implementation of the LSS program was able to enhance the performance standards of pre-hospital emergency in the personnel and equipment dimensions, and overall. Hence, the use of this method is recommended in other centers and other dimensions affecting the performance standards of pre-hospital emergency.